The Performance of the Austin Indie Scene in Slacker: From the Body of a Scene to the Body of a Generation - Soldani, Maria Teresa (Imaginations: Journal of Cross-Cultural Image Studies, 2017)
Abstract | Slacker (1991) by Richard Linklater is considered a milestone in American independent cinema (King). The film is entirely shot on location in Austin, Texas, mainly in the area of the Drag. Its 24-hour narration of city life has specific features: a script conceived as a “Roadmap,” with no main characters or turning points; members of the scene and film crew as non-professional actors; and local Austin music. This article explores Slacker’s unique representation of the local indie scene and how its collective performance became emblematic of a generational phenomenon, thus shifting the culture discourse’s emphasis from space (Austin) to time (Generation X). Résumé | Slacker (1991) de Richard Linklater est considéré comme un jalon d’une importance clé dans le cinéma indépendant américain (King, 2005). Le film en entier a été tourné à Austin au Texas, principalement dans le voisinage de la Drag. La narration de 24 heures de la vie urbaine possède des caractéristiques particulières : un scénario conçu comme une « feuille de route », sans personnages principaux ou moments charnières; des membres de l’équipe de mise en scène et de tournage comme acteurs non professionnels; de la musique d’Austin. Cet article explore la représentation unique de Slacker de la scène indépendante locale et de quelle façon sa performance collective est devenue emblématique d’un phénomène générationnel, en mettant l’accent non plus sur l’espace (Austin), mais sur le temps (Génération X).